Broad Severe Acute Respiratory Syndrome Coronavirus 2 Cell Tropism and Immunopathology in Lung Tissues From Fatal Coronavirus Disease 2019 - Ramos da Silva, Suzane; Ju, Enguo; Meng, Wen; Paniz Mondolfi, Alberto E; Dacic, Sanja; Green, Anthony; Bryce, Clare; Grimes, Zachary; Fowkes, Mary; Sordillo, Emilia M; Cordon-Cardo, Carlos; Guo, Haitao; et al. (The Journal of infectious diseases, 2021)
Abstract Background Coronavirus disease 2019 (COVID-19) patients manifest with pulmonary symptoms reflected by diffuse alveolar damage (DAD), excessive inflammation, and thromboembolism. The mechanisms mediating these processes remain unclear. Methods We performed multicolor staining for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins and lineage markers to define viral tropism and lung pathobiology in 5 autopsy cases. Results Lung parenchyma showed severe DAD with thromboemboli. Viral infection was found in an extensive range of cells including pneumocyte type II, ciliated, goblet, club-like, and endothelial cells. More than 90% of infiltrating immune cells were positive for viral proteins including macrophages, monocytes, neutrophils, natural killer (NK) cells, B cells, and T cells. Most but not all infected cells were angiotensin-converting enzyme 2 (ACE2) positive. The numbers of infected and ACE2-positive cells are associated with extensive tissue damage. Infected tissues exhibited high levels of inflammatory cells including macrophages, monocytes, neutrophils, and NK cells, and low levels of B cells but abundant T cells consisting of mainly T helper cells, few cytotoxic T cells, and no regulatory T cells. Robust interleukin-6 expression was present in most cells, with or without infection. Conclusions In fatal COVID-19 lungs, there are broad SARS-CoV-2 cell tropisms, extensive infiltrated innate immune cells, and activation and depletion of adaptive immune cells, contributing to severe tissue damage, thromboemboli, excess inflammation, and compromised immune responses. We provide an atlas of lung immunopathology of fatal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, revealing unexpected broad cell tropism and infection of parenchymal, endothelial, and immune cells by SARS-CoV-2, which are associated with massive tissue damage and thromboemboli.